2016
DOI: 10.1142/s0192415x16500403
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA Protects Against Folic Acid-Induced Acute Kidney Injury

Abstract: Tanshinone IIA is a diterpene extracted from Salvia miltiorrhiza, a popular and safe herb medicine that has been widely used in China and other Asian countries. Previous studies have demonstrated the pleiotropic effects of Tanshinone IIA on many disease treatments via its antitoxicity, anti-inflammation, anti-oxidative stress, as well as antifibrosis activities. However, its effect on acute kidney injury (AKI) has not been fully investigated. Here, we show for the first time that systemic administration of Tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Terpen glycosides from Cortex Moutan, the root bark of Paeonia suffruticosa , reduced inflammatory cytokines including IL-6, MCP-1, and intercellular adhesion molecule 1 (ICAM-1), in a rat model of diabetic nephropathy [98]. In a folic acid-induced kidney injury model in mice, systemic administration of Tanshinone IIA, a diterpene and one of the abundant constituents of Salvia Miltiorrhiza , resulted in improved kidney function with a concomitant reduction in chemokine expression [99]. Tanshinone IIA also suppressed renal fibrosis and inflammation as assessed by a decrease in cytokines TNF-α, MCP-1, and the chemokine CXCL-1, in a rat model of CKD induced by nephrectomy [100].…”
Section: Inflammationmentioning
confidence: 99%
“…Terpen glycosides from Cortex Moutan, the root bark of Paeonia suffruticosa , reduced inflammatory cytokines including IL-6, MCP-1, and intercellular adhesion molecule 1 (ICAM-1), in a rat model of diabetic nephropathy [98]. In a folic acid-induced kidney injury model in mice, systemic administration of Tanshinone IIA, a diterpene and one of the abundant constituents of Salvia Miltiorrhiza , resulted in improved kidney function with a concomitant reduction in chemokine expression [99]. Tanshinone IIA also suppressed renal fibrosis and inflammation as assessed by a decrease in cytokines TNF-α, MCP-1, and the chemokine CXCL-1, in a rat model of CKD induced by nephrectomy [100].…”
Section: Inflammationmentioning
confidence: 99%
“…Tanshinone IIA is used for treating cardiovascular diseases including cardiac hypertrophy, heart failure and myocardial ischaemia‐reperfusion injury, which could improve heart function by reducing the degree of fibrosis and inhibiting the apoptosis of cardiomyocytes 9. It has been reported that tanshinone IIA is a popular and safe herb medicine, which showed a protective effect on the endothelial cells 10. In addition, tanshinone IIA has been shown to attenuate inflammatory pathways, increase the blood vessels, improve the haemodynamics, dilate the coronary arteries to increase perfusion and enhance myocardial contractility 11.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been reported that tanshinone IIA is a popular and safe herb medicine, which showed a protective effect on the endothelial cells. 10 In addition, tanshinone IIA has been shown to attenuate inflammatory pathways, increase the blood vessels, improve the haemodynamics, dilate the coronary arteries to increase perfusion and enhance myocardial contractility. 11 Nuclear factor kappa B (NF-jB) has been known to be a significant transcription factor in a living organism for the functioning of nearly all cells.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the present study revealed that tanshinone IIA significantly inhibited the increased levels of TNF-α, IL-1β and IL-6 in the SCP rats. Jiang et al also suggested that tanshinone IIA protects against folic acid-induced acute kidney injury through inhibition of the inflammatory response (17).…”
Section: Discussionmentioning
confidence: 99%